Bulk prepolymerization of styrene in the presence of polybutadiene: Determination of grafting efficiency by size exclusion chromatography combined with a new extended model - Casis, Natalia (2009)
The bulk prepolymerization of styrene in the presence of polybutadiene for the production of highimpact polystyrene is analyzed and compared with an equivalent solution reaction described by Estenoz et al. in 1999. The heterogeneous model reported by Casis et al. in 2006 is extended to predict the bivariate distributions of the graft copolymer topologies; each topology is characterized by the number of trifunctional branching points per molecule. The developed model assumes polymerization in two phases and requires the adjustment of a single kinetic parameter. Grafting efficiencies determined by solvent extraction/gravimetry are compared with determinations obtained by the deconvolution of size exclusion chromatograms of the total polymer. The chromatographic technique is fast and simple, but it requires a representative polymerization/fractionation model.